(untitled) (Bioagro, 2022)
Citrus x latifolia Tanaka ex Q. Jiménez or Tahiti lime has a significant percentage within the citrus chain in Colombia. Schizotetranychus hindustanicus or hindu mite, produces typical lesions in the upper part of the leaves and fruits, characterized by circular whitish spots (1 to 3 mm in diameter), which correspond to the cobwebs or nests that the female weaves, reducing the aesthetic value of the fruit and its commercialization. The objective of this study was to evaluate in vitro the acaricidal effects of different chemical compounds through three contact times on populations of S. hindustanicus. The following were evaluated: the oleaginous extract of Neem-Azadirachta indica al 1,0 %, 0.5 % micronized sulfur, 0.4% soluble extract of Azadirachtin, 15 % ash broth filtrate, and a control of Abamectin 0.2 %, recognized for its acaricidal effect. Water distilled was used as a negative control. It was evidenced that the most effective treatments were: Neem-A. indica oleaginous extract at 1.0 %, micronized sulfur at 0.5 %, and Abamectin at 0.2 % with mortality values of 96.4, 97.9 and 100 % at 72 h, respectively. The results obtained in this work allow suggesting the use of natural compounds based on Azadirachta indica in oleaginous solutions for the control of S. hindustanicus, they do not affect the ecosystem and resistance to it has not been reported.